Legal Politics of Environmental Licensing Governance After Job Creation Law - Nabila Aulia Rahman; Zainal Arifin Mochtar; Ilham Dwi Rafiqi; Mohamed Yayah Jalloh (Fakultas Hukum Universitas Hang Tuah, 2022)
The validation of the Job Creation Law in Indonesia brought many fundamental changes in economic policy, including environmental licensing. It is because of a fundamental legal political changes that more directed to the ease of doing business and investing compared to the environmental conservation, by changing the terminology of environmental licensing to environmental approval. This paper aims to analyze the legal politics of environmental licensing governance after the Job Creation Act. The results of this study indicated that there are changes in legal politics in environmental licensing governance after the Job Creation Law which had implications for the business licensing system. So, a legal mapping is needed regarding to the concept of environmental licensing in the Job Creation Act. The findings of this paper are the ideal concept of environmental licensing based on the 1945 Constitution of the Republic of Indonesia.